Kognitivno-vedenjska obravnava samopoškodbenega vedenja v mladostništvu - Dolenc, Barbara (Psihološka obzorja (Ljubljana), 2020)
The purpose of this paper is to present cognitive-behavioural strategies for dealing with adolescents with deliberate selfharm. The presented interventions can be useful for anyone who is faced with that kind of problem in the clinical setting. Deliberate self-harm is defined as self-injury and self-poisoning. It usually occurs between the ages of 11 and 15 years. During adolescence, the prevalence of this type of behaviour is between 12 and 23%. The frequency of such behaviour is even greater among the clinical population. The most powerful risk factor for deliberate self-harm is the presence of mental disorder. Adolescents often report of chronic feelings of emptiness, alienation and isolation, of hopelessness, helplessness, of being unloved, of low self-esteem and a low tolerance for stress. The increased risk of deliberate self-harm is mainly related to emotional dysregulation and poor problem solving skills. If adolescents with deliberate self-harm do not seek help, self-inflicted behaviour may increase in its severity. It also represents a strong predictor of suicide; therefore, therapeutic intervention is of utmost importance. When dealing with deliberate self-harm, cognitive-behavioural therapy has proven to be one of the effective methods of treatment. Within therapy, the emphasis is on emotion regulation, dealing with dysfunctional thoughts and beliefs, reinforcing behavioural skills (such as problem solving skills) and improving interpersonal relationships. Moreover, much attention is paid to a mindful attitude towards oneself and one's own past. Research shows that after completed treatment, adolescents reported less frequent self-harm behaviour and suicidal thoughts. At the same time, symptoms of depression and anxiety were reduced and adolescents reported of more positive self-image, better emotion regulation and better problem solving skills.
Keywords: adolescents; cognitive behavior therapy; kognitivno vedenjska terapija; mladostniki; samopoškodbeno vedenje; self-injurious behavior